Overview of Emotion Regulation in Vocational High School Students in Surabaya: Gambaran Regulasi Emosi pada Siswa Sekolah Menengah Kejuruan di Surabaya - Rahmansyah, Huda; Affandi, Ghozali Rusyid (Psikologia : Jurnal Psikologi, 2023)
Emotion regulation is an individual's way of consciously or unconsciously to maintain, strengthen or reduce one or more aspects of emotional responses in which there is an experience of emotion and behavior. Adolescence is a period of transition to adulthood whose emotions fluctuate and are less able to express emotions in the right way. Emotional regulation in late teens is found in the fact that they are less able to regulate emotion properly, indicated by aggressive behavior, apathy towards the environment, free sex, drugs, and even withdrawal. Emotion regulation is influenced by physiological aspects, subjective experiences of individuals and responses to existing emotions. The purpose of this study is to describe the emotional regulation of students at SMK X Surabaya. The subjects in this study amounted to 153 people with Non-Probality sampling technique with quota sampling method. Subject criteria are students of SMK X Surabaya. The data collection method used the Emotion Regulation scale. Data analysis used descriptive statistics to analys just one variable wich is emotion regulation in SMK X Surabaya with the results of 6 students with a percentage of 4% having very high emotional regulation, 116 students having high emotional regulation with a percentage of 76%, 31 students having low regulation with a percentage of 20% and no students having very low regulation so that the percentage is 0%.